Online Green Entrepreneurship Education: Exploring Competencies, Intentions, and Learning Barriers - Eka Imbia Agus Diartika; Zahid Zufar at Thaariq (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to explore students’ green entrepreneurial competencies, entrepreneurial intentions, and learning barriers within the implementation of Online-Based Green Entrepreneurship Education (GEE) in higher education. This study conducted a preliminary qualitative exploration of the model implementation through semi-structured interviews with lecturers and open-ended questionnaires administered to students in an online Bioentrepreneurship course. Thematic analysis was conducted to assess entrepreneurial competencies, learning barriers, and entrepreneurial intentions. To ensure the credibility of the findings, source triangulation was employed by comparing and cross-validating themes derived from lecturer interviews and student open-ended questionnaire responses. The results indicate that students possess adequate basic knowledge and sustainability values; however, practical skills, systems-thinking abilities, and real-world entrepreneurial experience remain limited due to the characteristics of online learning and restricted access to hands-on activities. The main barriers include financial constraints, lack of green facilities, limited understanding of markets and policies, and insufficient mentoring support. Although students demonstrate positive green entrepreneurial intentions, a gap between intention and actual behavior persists, influenced by low self-efficacy and weak structural support. These findings highlight the importance of improving the implementation of online GEE to better support students’ green entrepreneurial competencies, intentions, and entrepreneurial readiness in higher education.